Pollution and damage to land resources of Ukraine as a sign of criminal offenses against peace, human security and international law and order in the context of russian military aggression - Shulha, Andrii (ScienceRise: Juridical Science, 2023)
The article deals with the issues related to the legal protection of land resources of Ukraine, which were significantly negatively affected during the military aggression and hostilities by the so-called rusian federation. The article identifies and analyzes the types of pollution and damage to land resources arising from military aggression and hostilities by the rusian federation as an aggressor country. Such pollution and damage to land resources is called military-technogenic pollution of land resources. It is stated, that the conduct of not only active but also passive hostilities causes irreparable damage to land resources. This is manifested in mechanical, physical, chemical, and biological contamination of the soil cover of lands of various categories. Also, for example, digging trenches, fortified areas, ammunition and personnel storage facilities, and caponiers for military equipment causes degradation of the soil cover. The consequences of these actions indicate the presence of signs of such a criminal offense as "Ecocide" – Article 441 of the Criminal Code of Ukraine. It is concluded, that: 1) military-technogenic contamination of the soil cover causes direct soil contamination with hazardous substances of a military nature, as well as their degradation; 2) such consequences are socially dangerous for humans and the environment, given the system of interaction "soil-plant", "soil-plant-human" 3) in general, such contamination of the soil cover should be classified under Article 441 "Ecocide" of the Criminal Code of Ukraine without applying the provisions of Section VIII "Criminal Offenses Against the Environment"; 4) the establishment of the evidence base should be carried out by joint efforts of national and international law enforcement agencies; 5) compensation for the damage, caused by the pollution and damage to land resources, should be made by way of contribution and reparation from rusia as the aggressor state